2019
DOI: 10.1016/j.biortech.2019.01.044
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Thermostable xylanases from thermophilic fungi and bacteria: Current perspective

Abstract: Thermostable xylanases from thermophilic fungi and bacteria have a wide commercial acceptability in feed, food, paper and pulp and bioconversion of lignocellulosics with an estimated annual market of USD 500 Million. The genome wide analysis of thermophilic fungi clearly shows the presence of elaborate genetic information coding for multiple xylanases primarily coding for GH10, GH11 in addition to GH7 and GH30 xylanases. The transcriptomics and proteome profiling has given insight into the differential express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 91 publications
1
59
0
1
Order By: Relevance
“…The xylanase is ubiquitous in nature and its presence is observed diversely in a wide range of living organisms, such as marine, terrestrial and rumen bacteria (Chakdar et al 2016), thermophilic and mesophilic fungi (Chadha et al 2019;Singh et al 2019), protozoa (Devillard et al 1999;Béra-Maillet et al 2005), crustaceans (Izumi et al 1997), snails (Suzuki et al 1991), insects (Brennan et al 2004), algae (Jensen et al 2018), plants and seeds (immature cucumber seeds and germinating barley) (Bae et al 2008;Sizova et al 2011). Bacteria and fungus are widely used for industrial production of xylanase.…”
Section: Source For Xylanase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The xylanase is ubiquitous in nature and its presence is observed diversely in a wide range of living organisms, such as marine, terrestrial and rumen bacteria (Chakdar et al 2016), thermophilic and mesophilic fungi (Chadha et al 2019;Singh et al 2019), protozoa (Devillard et al 1999;Béra-Maillet et al 2005), crustaceans (Izumi et al 1997), snails (Suzuki et al 1991), insects (Brennan et al 2004), algae (Jensen et al 2018), plants and seeds (immature cucumber seeds and germinating barley) (Bae et al 2008;Sizova et al 2011). Bacteria and fungus are widely used for industrial production of xylanase.…”
Section: Source For Xylanase Productionmentioning
confidence: 99%
“…Thielavia terrestris, (Garcia-Huante et al 2017), Talaromyces thermophilus (Maalej et al 2009), Paecilomyces thermophile (Fan et al 2012), Achaetomium sp. X2-8 (Chadha et al 2019), Rhizomucor pusillus (Hüttner et al 2018), Rasamsonia emersonii, (Martínez et al 2016) T. Leycettanus (Wang et al 2017), Melanocarpus albomyces (Gupta et al 2013) and Aspergillus oryzae LC1 (Bhardwaj et al 2019) were found to be producer of hyper-thermophilic active xylanase. Several alkali stable xylanases were obtained from different fungal strains such as Paenibacillus barcinonensis (Valenzuela et al 2010), Aspergillus fumigatus MA28 (Bajaj and Abbass 2011), Cladosporium oxysporum (Guan et al 2016) and Aspergillus oryzae LC1 (Bhardwaj et al 2019).…”
Section: Fungal Sources Of Xylanasesmentioning
confidence: 99%
“…Hence, enzyme saccharification would be a great choice of hydrolysis for hemicellulose to avoid toxic inhibitors. Apart from biorefinery, xylanases have a potential industrial application in various fields like wine making, textile, paper and pulp industries, animal husbandry, bread making, fruit juice extraction (Chadha et al, 2019) etc. Production of xylanases in large scale is gaining much importance in getting the scope to cut down the enzyme cost with the use of high yielding microbes (Ramanjaneyulu and Rajasekhar Reddy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Production of xylanases in large scale is gaining much importance in getting the scope to cut down the enzyme cost with the use of high yielding microbes (Ramanjaneyulu and Rajasekhar Reddy, 2016). Xylanase production by various organisms have been studied like fungi (Chadha et al, 2019), bacteria (Kumar et al, 2018), yeast, (Ergun and Çalık, 2016), and even with co-culture of more than one organism (Yardimci and Cekmecelioglu, 2018). Among them, fungi have been found to be potent xylanase producers and therefore many filamentous fungi have been reported for the production of xylanase.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of the microbial xylanases falls into family 10 (GH10) or family 11 (GH11). GH10 xylanases regularly have a high molecular weight (≥30 kDa) with a (β/α) 8 fold TIM barrel structure (Rahmani et al ., ), while GH11 xylanases are generally low molecular weight proteins (<30 kDa) with a β‐jelly‐roll fold structure (Chadha et al ., ).…”
Section: Introductionmentioning
confidence: 97%